The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s10995-012-1139-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Pre-pregnancy BMI, Gestational Weight Gain, and Age at Menarche in Daughters

Abstract: Objectives Life course theory suggests that early life experiences can shape health over a lifetime and across generations. Associations between maternal pregnancy experience and daughters’ age at menarche are not well understood. We examined whether maternal pre-pregnancy BMI and gestational weight gain (GWG) were independently related to daughters’ age at menarche. Consistent with a life course perspective, we also examined whether maternal GWG, birth weight, and prepubertal BMI mediated the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
56
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 59 publications
10
56
1
1
Order By: Relevance
“…In our analysis, child's weight and maternal BMI were more strongly associated with the OR of thelarche and child's height and weight were the only variables significantly associated with breast development at 12.9 years. These findings are consistent with studies showing earlier breast development among girls with greater BMI and accelerated achievement of pubertal milestones among both male and female offspring of overweight or obese mothers [34,35]. One potential mechanism for the effect of dairy consumption on thelarche in this population is that it is often associated with lower weight and adiposity in observational studies [36].…”
Section: Discussionsupporting
confidence: 90%
“…In our analysis, child's weight and maternal BMI were more strongly associated with the OR of thelarche and child's height and weight were the only variables significantly associated with breast development at 12.9 years. These findings are consistent with studies showing earlier breast development among girls with greater BMI and accelerated achievement of pubertal milestones among both male and female offspring of overweight or obese mothers [34,35]. One potential mechanism for the effect of dairy consumption on thelarche in this population is that it is often associated with lower weight and adiposity in observational studies [36].…”
Section: Discussionsupporting
confidence: 90%
“…Whether these factors could alter the onset of puberty is uncertain. Prepregnant overweight and obesity have been related to younger age at menarche in some cohort investigations (23,50); nevertheless, this association may not necessarily represent a causal effect but could instead be a result of shared genetic or environmental factors. One study reported a weak, U-shaped association between gestational weight gain and the risk of early menarche in the offspring (10), but this relation was not independent of prepregnancy weight in another investigation (23).…”
Section: Prenatal Nutritionmentioning
confidence: 99%
“…Given rising obesity and growing evidence that GWG may contribute to setting the trajectory for poor health throughout life (12), the association between excessive GWG and large for gestational age and macrosomic infants has raised concern about children's subsequent increased risks for metabolic disorders and obesity (12-14), early menarche (15), and cardiovascular disease in adulthood (16). In mothers, excessive GWG is associated with antenatal and intra-partum complications (4) and obesity postpartum (4,13,14) and later in life (17,18).…”
mentioning
confidence: 99%